Effects of conflict of interest on the choice between robo advisors and financial advisors : an experimental approach - Mok, Christopher (Nanyang Technological University, 2021)
Financial planning is beneficial to improve the financial well-being of individuals, but many do not seek financial advice to improve their portfolio efficiency. With the disruption of Robo Advisors (Robo) in the financial advisory industry, it is unclear how the lack of human touch in digital advisors compared to traditional Financial Advisors (FAs) appeals to investors. To investigate how Conflict of Interest (COI) in the financial advisory industry affects the type of financial advice demanded by investors, we designed and implemented a multi-period portfolio choice experiment where investors manage a portfolio of a risky asset and a risk-free asset with the additional option of investing using Robo or FA. Our findings suggest that FAs are more likely to provide false advice when there is a higher intensity of COI. They also suggest that the level of competition in the financial advisory industry affects the extent of substitution from traditional FAs to Robo and how likely investors follow the advice of FAs. Overall, our findings provide evidence to COI as a determinant for the preference of the lack of human touch in the provision of financial advice. This paper contributes to the existing work on behavioural household finance and further shed light on the demand of financial advice in the presence of Robo.